Fluid Geochemistry Contribution to the Interpretation of the 2011–2012 Unrest of Santorini, Greece, in the Frame of the Dynamics of the Aegean Volcanic Arc. Issue 3 (23rd March 2019) - Tarchini, L.; Carapezza, M. L.; Ranaldi, M.; Sortino, F.; Gattuso, A.; Acocella, V.
Abstract: Tectonic and magmatic activity may couple at volcanic arcs, even though any relationship is less defined in smaller arcs, experiencing limited activity. Here we use gas geochemistry data collected during the 2011–2012 unrest at Santorini (Greece) to understand better the dynamics of the Aegean Volcanic Arc with regard to its tectonic setting. Since the most recent eruption in 1950 and before the unrest, minor seismicity and CO2 degassing (mainly from the fumaroles of Nea Kameni islet) were observed at Santorini. On January 2011, anomalous seismicity along the NE‐SW trending Kameni Line was accompanied by an inflation north of Nea Kameni. Fumarolic gas composition changed and gas release notably increased. We carried out geochemical study on both Kameni and Thera islands from January 2012 to June 2013. We repeated surveys of diffuse soil CO2 degassing and of in‐soil gas concentration, and we analyzed fumaroles and gas dissolved in thermal waters for chemical and isotopic composition. In agreement with previous studies, our geochemical data, particularly the diffuse soil CO2 flux increase, the increase of H2 content, and of CO2 /CH4 and 3 He/ 4 He ratios in fumarolic gases, support geophysical data in indicating that unrest was associated with the emplacement of new mafic magma. This unrest had limited effect on the regional setting, with gas emissions focusing along the regional NE‐SW structures, without triggering by any seismic event, conversely to the 1950 eruption, which probably occurred in a frame of general tectonic reorganization of the Aegean microplate. Key Points: Extensive and systematic geochemical surveys followed the anomalous degassing during Santorini unrest, both in the caldera center and on the inner caldera walls Gas ratios and isotopic composition indicate deep mafic magma refilling into the shallow dacitic plumbing system Unrest has limited apparent relations with the longer‐term tectonic evolution of the Arc, conversely to the 1950 eruption